ЭВОЛЮЦИЯ МОСКОВСКО-ВАЛДАЙСКИХ ПАЛЕОВРЕЗОВ МЕЖДУРЕЧИЙ СРЕДНЕРУССКОЙ ВОЗВЫШЕННОСТИ - Сычева С.А. (My University, 2003)
Several examples of buried erosion landforms uncovered in the Lebedinsky quarry (Kursk magnetic anomaly) were examined. They are situated within the valley-balka slope of river Oscolets and adjacent lower part of watershed. The structure of sediments that fill the depressions represents full erosion cycle corresponding to climatic rhythm: the end of Moscow glaciation, Miculino interglacial, beginning of Valdai glaciation. Taken as a whole erosion cycle consists of the incision stage (arid climate - periglacial, then interglacial), stabilisation stage (humid climate of interglacial and Valdai interstadials), accumulation stage (cold humid and then periglacial climate). Detailed picture of erosion cycle is much more complex and has hierarchical structure connected with hierarchy of Pleistocene climatic rhythms.
Keywords: Pleistocene; 551.4.075(234.81); Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен